The Process Of Washing Tableware At Culinary Tourism Centers - Vionabella, Maura; Rusmiati, Rusmiati; Sari, Ernita; Suprijandani, Suprijandani (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Culinary Tourism Centers must ensure proper tableware washing processes to prevent health risks. Preliminary tests on 12 tableware vendors at the Culinary Tourism Center found that 6 sets of utensils did not meet quality standards. This study aimed to assess the washing process of tableware in the Culinary Tourism Center. The research was descriptive, with purposive sampling. Data collection involved observations and laboratory tests, analyzed descriptively using tables, narratives, and summaries. Laboratory test results showed that several types of tableware, including plates, spoons, forks, and glasses, had germ counts exceeding the standard limits. The bacteriological quality of the clean water used also did not meet requirements, with Total Coliform levels reaching 48 CFU/m². Observation findings revealed that 40% of washing practices failed to meet qualifications due to noncompliance with established procedures. The study concludes that both the bacteriological quality of certain tableware and the clean water used for washing are below acceptable standards. In addition, some washing processes remain unqualified according to the prescribed guidelines. It is recommended that vendors pay greater attention to proper tableware washing techniques, improve their knowledge and practices, and routinely drain water storage tanks to maintain water quality.